2022
DOI: 10.3389/fpsyt.2022.827536
|View full text |Cite
|
Sign up to set email alerts
|

Theta oscillations: A rhythm difference comparison between major depressive disorder and anxiety disorder

Abstract: BackgroundDue to substantial comorbidities of major depressive disorder (MDD) and anxiety disorder (AN), these two disorders must be distinguished. Accurate identification and diagnosis facilitate effective and prompt treatment. EEG biomarkers are a potential research hotspot for neuropsychiatric diseases. The purpose of this study was to investigate the differences in EEG power spectrum at theta oscillations between patients with MDD and patients with AN.MethodsSpectral analysis was used to study 66 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Our experiment found that higher values for Low θ power were not specific to the PTSD phenotype but were markers of non-resilient phenotypes (C1 and C2), and, conversely, lower values were a hallmark of resilience. Our result is in line with earlier observations of increased frontal θ power in MDD (Arns et al, 2015 ; Zhang et al, 2022 ), demonstrating that this biomarker is not specific to a pathology. However, our study goes further and shows that ECoG differences can be observed before stress exposure and can be used to predict phenotypes.…”
Section: Discussionsupporting
confidence: 94%
“…Our experiment found that higher values for Low θ power were not specific to the PTSD phenotype but were markers of non-resilient phenotypes (C1 and C2), and, conversely, lower values were a hallmark of resilience. Our result is in line with earlier observations of increased frontal θ power in MDD (Arns et al, 2015 ; Zhang et al, 2022 ), demonstrating that this biomarker is not specific to a pathology. However, our study goes further and shows that ECoG differences can be observed before stress exposure and can be used to predict phenotypes.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies searching for a physiological biomarker have primarily focused on periodic, oscillatory data, eliminating the aperiodic component by normalizing power band signals to a baseline period for trial-level analyses in task-based designs 32 , or by regressing out the negative linear slope with techniques such as IRASA 33 and FOOOF 34 . These studies have identified potential biomarkers for treatment response and mood in various frequency bands (theta 11 , alpha 9,10 , beta 7,9 , high and low gamma 7,9,35 ) across affective regions. However, the wide variety of reported frequency bands may all be driven by a common underlying phenomenon – a change in the power law slope across all frequency bands.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies found increased frontal–midline theta power in the resting state in MDD patients; this increase was located in the anterior cingulate cortex (ACC) and reflected impaired emotion regulation ( Jaworska et al, 2012 ). However, some following studies did not replicate this finding and even found an opposite abnormal pattern ( Jiang et al, 2016 ; Zhang Y. et al, 2022 ). Besides, some other studies have reported that the abnormal frontal theta asymmetry could be used as a biomarker to distinguish MDD patients from health populations ( Kwon et al, 1996 ; Dharmadhikari et al, 2018 ), but its functional correlate is still unclear.…”
Section: The Neural Mechanisms Of Tacs For Treating Mddmentioning
confidence: 91%
“…Regarding theta power, two recent perspectives are worth noting. First, recent studies have suggested that abnormalities in theta band power are more related to anxiety than to depression ( Gold et al, 2013 ; Zhang Y. et al, 2022 ); thus, the direct relationship between theta power abnormalities and MDD may require further studies to elucidate. Second, the interarea synchronization of theta power is critical for long-range information exchange ( Reinhart and Nguyen, 2019 ), and recent studies have found that global theta synchronization is abnormally increased in individuals with depression compared to healthy individuals during the resting state and performance of emotion regulation tasks ( Xing et al, 2017 , 2019 ).…”
Section: The Neural Mechanisms Of Tacs For Treating Mddmentioning
confidence: 99%